Electrolytic capacitor and its manufacturing method

The electrolytic capacitor design with a separator containing synthetic fibers and cellulose fibers, and unevenly distributed hydroxyl group-containing compounds, addresses the need for improved performance by enhancing adhesion of the conductive polymer, resulting in low ESR and high voltage resistance.

JP7620827B2Active Publication Date: 2025-01-24PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021014006
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-29
Publication Date
2025-01-24
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

There is a demand for electrolytic capacitors with higher characteristics such as low equivalent series resistance (ESR), high voltage resistance, and improved reliability.

Method used

The electrolytic capacitor design includes an anode foil with a dielectric layer, a cathode foil, and a separator interposed between them, where the separator contains synthetic fibers and cellulose fibers, with a hydroxyl group-containing compound like sugars or polyhydric alcohols unevenly distributed to enhance adhesion of a conductive polymer, improving the capacitor's performance.

Benefits of technology

The design results in an electrolytic capacitor with low ESR, high voltage resistance, and improved reliability, as evidenced by the manufacturing examples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620827000002
    Figure 0007620827000002
  • Figure 0007620827000003
    Figure 0007620827000003
  • Figure 0007620827000001
    Figure 0007620827000001
Patent Text Reader

Abstract

To enhance the characteristic of an electrolytic capacitor.SOLUTION: An electrolytic capacitor comprises a capacitor element including: an anode foil having a dielectric layer on its surface; a cathode foil; a separator interposed between the anode foil and cathode foil; a hydroxyl group-containing compound; and a conductive polymer. The separator contains synthetic fibers and cellulose-based fibers. The conductive polymer and the hydroxyl group-containing compound deposit to the surface and inside of the separator. The hydroxyl group-containing compound is composed of at least one compound selected from a group consisting of sugar alcohol and polyhydric alcohol (excluding polymer). In the separator, the hydroxyl group-containing compound is unevenly distributed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing the same. [Background technology]

[0002] Capacitors used in electronic devices are required to have a large capacity and a small equivalent series resistance (ESR) value in the high frequency range. Electrolytic capacitors using conductive polymers such as polythiophene are promising capacitors with a large capacity and low ESR. The capacitor element of an electrolytic capacitor is obtained, for example, by winding an anode foil and a cathode foil with a separator between them to form an electrode group, and impregnating the electrode group with a dispersion of a conductive polymer.

[0003] Patent Document 1 discloses a separator for use in solid electrolytic capacitors, which is constructed by dissolving cellulose in a solvent, applying a DC voltage to a nozzle that sprays the solution, and depositing long fibers with a fiber diameter of 1 μm or less. Patent Document 1 also discloses a separator constructed by dissolving a synthetic resin such as polyethylene terephthalate (PET) or aramid in an organic solvent or water, and applying a DC voltage to a nozzle that sprays the solution, and depositing long non-fibrillated fibers with a fiber diameter of 1 μm or less.

[0004] Patent Document 2 discloses a separator for use in an electrochemical element, which contains 20-80% by mass of natural cellulose fiber A, 10-50% by mass of natural cellulose fiber B, and 10-50% by mass of beaten regenerated cellulose fiber. The natural cellulose fiber A has a length-weighted average fiber length of 0.30-1.19 mm and a CSF of 500-50 ml. The natural cellulose fiber B has a length-weighted average fiber length and a maximum distribution fiber length of 1.20-1.99 mm and a CSF of 500-50 ml. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2010-245150 A [Patent Document 2] International Publication No. 2017 / 047699 Brochure Summary of the Invention [Problem to be solved by the invention]

[0006] Currently, there is a demand for electrolytic capacitors with higher characteristics (eg, low ESR, high voltage resistance and reliability, etc.). [Means for solving the problem]

[0007] One aspect of the present invention relates to an electrolytic capacitor comprising: an anode foil having a dielectric layer on a surface thereof, a cathode foil, a separator interposed between the anode foil and the cathode foil, a capacitor element including a hydroxyl group-containing compound and a conductive polymer, wherein the separator includes synthetic fibers and cellulosic fibers, the conductive polymer and the hydroxyl group-containing compound are adhered to a surface layer and an interior of the separator, the hydroxyl group-containing compound is at least one compound (excluding polymers) selected from the group consisting of sugars and polyhydric alcohols, and the hydroxyl group-containing compound is unevenly distributed in the separator.

[0008] Another aspect of the present invention relates to a method for producing an electrolytic capacitor, comprising: a first step of obtaining an intermediate including an anode foil having a dielectric layer on a surface thereof, a cathode foil, a separator interposed between the anode foil and the cathode foil, and a hydroxyl-containing compound adhered to a surface layer and an interior of the separator and unevenly distributed in the separator; and a second step of impregnating the intermediate with a treatment liquid including a conductive polymer to obtain the capacitor element, wherein the separator includes synthetic fibers and cellulosic fibers, and the hydroxyl-containing compound is at least one compound (excluding polymers) selected from the group consisting of sugars and polyhydric alcohols. Effect of the Invention

[0009] According to the present invention, an electrolytic capacitor with excellent characteristics can be obtained. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view illustrating an example of an electrolytic capacitor according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a perspective view showing a part of the wound body of FIG. 1 in a developed form. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Electrolytic capacitor] The electrolytic capacitor according to the embodiment of the present invention includes an anode foil having a dielectric layer on its surface, a cathode foil, a separator interposed between the anode foil and the cathode foil, a hydroxyl-containing compound, and a capacitor element including a conductive polymer. The separator includes synthetic fibers and cellulosic fibers. The conductive polymer and the hydroxyl-containing compound are attached to the surface and interior of the separator. Hereinafter, the anode foil, the cathode foil, and the separator are collectively referred to as an "electrode group."

[0012] The hydroxyl group-containing compound is at least one compound selected from the group consisting of sugars and polyhydric alcohols. However, the hydroxyl group-containing compound does not include polymers. For example, polymers that may be included in the category of polyhydric alcohols are excluded. Examples of the polymer include polyvinyl alcohol (PVA) and polyalkylene oxides having alcoholic hydroxyl groups at their terminals. The polymer referred to here is not particularly limited, but means, for example, a molecule having a weight average molecular weight of 1000 or more.

[0013] The hydroxyl-containing compound is unevenly distributed in the separator. "The hydroxyl-containing compound is unevenly distributed in the separator" means that the hydroxyl-containing compound is distributed in a higher concentration inside the separator than in the surface layer of the separator. The surface layer of the separator refers to a very thin region including the outer surface of the separator, and the maximum depth of the surface layer from the outer surface of the separator is, for example, 25% or less of the thickness of the separator. The concentration of the hydroxyl-containing compound in the surface layer of the separator is easily affected by the concentration of the hydroxyl-containing compound outside the separator, and can also be said to represent the concentration of the hydroxyl-containing compound outside the separator.

[0014] The separator is a porous sheet made of fibers. The hydroxyl-containing compound and conductive polymer attached to the inside of the separator means the hydroxyl-containing compound and conductive polymer attached to the wall surface inside the pores of the separator. The hydroxyl-containing compound and conductive polymer attached to the surface of the separator means the hydroxyl-containing compound and conductive polymer attached to the surface of the separator facing the anode foil or cathode foil. When the capacitor (electrode group) is disassembled and the cathode foil is taken out, the hydroxyl-containing compound and conductive polymer attached to the cathode foil can be regarded as the hydroxyl-containing compound and conductive polymer on the surface of the separator.

[0015] The hydroxyl groups of the hydroxyl-containing compound improve the adhesion of the conductive polymer. By distributing the hydroxyl-containing compound unevenly in the separator, the separator can stably hold a large amount of conductive polymer. In other words, the adhesiveness of the conductive polymer to the separator can be improved, and the conductive polymer can efficiently perform its role as an electrolyte. As a result, an electrolytic capacitor with good characteristics (especially low ESR) is obtained.

[0016] When a separator containing synthetic fibers and cellulosic fibers is used, an electrolytic capacitor with good characteristics (especially low ESR) can be obtained. Synthetic fibers are advantageous in terms of improving heat resistance and voltage resistance. Cellulosic fibers are advantageous in terms of improving the separator's ability to absorb a treatment solution containing a hydroxyl-containing compound. In other words, they are advantageous in terms of unevenly distributing the hydroxyl-containing compound in the separator (reducing ESR).

[0017] If the separator does not contain synthetic fibers and is made of cellulosic fibers, the separator has low strength and heat resistance, and is prone to short circuits when exposed to high temperatures, and has low voltage resistance. On the other hand, if the separator does not contain cellulosic fibers and is made of synthetic fibers, the hydroxyl-containing compound may not easily penetrate into the pores of the separator when the separator is impregnated with a treatment solution containing the hydroxyl-containing compound. In other words, it may be difficult to unevenly distribute the hydroxyl-containing compound on the separator, which may reduce the adhesion of the conductive polymer of the separator and increase the ESR.

[0018] In the capacitor element, the mass ratio M of the hydroxyl group-containing compound to the conductive polymer inside the separator I is the mass ratio M of the hydroxyl group-containing compound to the conductive polymer in the surface layer of the separator O It is preferable that the mass ratio M I Mass ratio M O Ratio:M O / M I may be 0.5 or more and 0.95 or less, or may be 0.7 or more and 0.9 or less.

[0019] The distribution of the hydroxyl group-containing compound in the capacitor element can be determined by the following method. (I) Disassemble the electrolytic capacitor, cut the separator to a specified size, and obtain a separator sample. Dry the separator sample, and then measure the mass of the dried separator sample. Extract the hydroxyl group-containing compound from the separator sample with ion-exchanged water.

[0020] (II) Separately, prepare a separator sample of the same size, and peel off the surface layer (or any attached matter on the surface) of the separator sample. The peeling method can be a method of thinly slicing the surface layer and removing it, a method of scraping it off, a method of applying adhesive tape to the surface layer and peeling it off, or the like. For the separator sample from which the surface layer has been removed, the mass of the separator sample is measured and the hydroxyl group-containing compound attached to the inside of the separator sample is extracted with ion-exchanged water in the same manner as above.

[0021] (III) The above mass ratio M I and mass ratio M O Looking for M O / M I M O / M I When the ratio is <1, it can be considered that the concentration of the hydroxyl group-containing compound is higher in the interior of the separator than in the surface layer.

[0022] The separator preferably contains 20 parts by mass or more and 60 parts by mass or less of cellulosic fibers (40 parts by mass or more and 80 parts by mass or less of synthetic fibers) per 100 parts by mass of the total of cellulosic fibers and synthetic fibers, and more preferably contains 20 parts by mass or more and 50 parts by mass or less of cellulosic fibers (50 parts by mass or more and 80 parts by mass or less of synthetic fibers).

[0023] (Separator) The separator can be produced by a papermaking method, and a mixed sheet containing synthetic fibers and cellulosic fibers can be used for the separator. The separator may be a woven fabric or a nonwoven fabric. The thickness of the separator is, for example, 20 μm or more and 200 μm or less. The separator may be formed by overlapping a plurality of fiber sheets. The plurality of fiber sheets may be of the same type or different types.

[0024] The cellulose-based fibers include natural cellulose fibers, etc. Examples of natural cellulose fibers include Manila hemp pulp, esparto pulp, softwood pulp, hardwood pulp, sisal pulp, etc. The cellulose-based fibers may also be regenerated cellulose fibers, semi-synthetic cellulose fibers, etc. The regenerated cellulose fibers include fibers spun using a solution in which natural cellulose is dissolved in a solvent (e.g., rayon). The semi-synthetic cellulose fibers include fibers made by adding other materials to natural cellulose to form fibers (e.g., acetate). One type of cellulose-based fiber may be used alone, or two or more types may be used in combination.

[0025] From the viewpoint of short circuit resistance, the cellulosic fibers may be fibrillated.

[0026] The synthetic fiber (fiber material) preferably contains at least one selected from the group consisting of aramid (aromatic polyamide), polyethylene terephthalate (PET), and vinylon (acetalized PVA). Among them, aramid is more preferable from the viewpoints of improving heat resistance and fiber strength (tensile strength). The synthetic fiber may be used alone or in combination of two or more kinds.

[0027] From the viewpoint of improving short-circuit resistance and absorbency of a treatment liquid containing a conductive polymer (reducing ESR), the synthetic fibers are preferably fibrillated. Fibrillation is performed by beating or the like.

[0028] In addition to the above-mentioned examples, the synthetic fiber (fiber material) may include polybutylene terephthalate, polyphenylene sulfide, nylon, polyimide, polyamideimide, polyetherimide, etc. The separator may include glass fiber.

[0029] The separator may be carbonized. The separator may be partially carbonized. The carbonization can appropriately reduce the density of the separator and increase the absorbency of the treatment liquid containing the conductive polymer. In the carbonization, the cellulose-based fibers are mainly carbonized.

[0030] The separator may include heat-sealable binder fibers. The separator may be heated to heat-seal the binder fibers, thereby bonding the fibers together.

[0031] (Hydroxy group-containing compound) The hydroxyl-containing compound is at least one compound selected from the group consisting of sugars and polyhydric alcohols, and does not contain a polymer. Since the hydroxyl-containing compound does not contain a polymer, it easily penetrates into the pores of the separator. Since the treatment liquid containing the hydroxyl-containing compound does not contain a polymer, it has a low viscosity and is easily impregnated into the separator.

[0032] Examples of sugars include glucose. Examples of polyhydric alcohols include mannitol, sorbitol, xylitol, pentaerythritol, and trimethylolpropane. Note that mannitol, sorbitol, xylitol, pentaerythritol, and the like are sometimes called sugar alcohols. Hydroxyl-containing compounds may be used alone or in combination of two or more.

[0033] The hydroxyl group-containing compound may be an organic compound containing multiple hydroxyl groups bonded to carbon atoms. The number of hydroxyl groups contained in the hydroxyl group-containing compound may be in the range of 2 to 12 (for example, in the range of 3 to 6). In general, the hydroxyl group-containing compound is a water-soluble compound. Note that PVA usually has 13 or more hydroxyl groups in a molecule.

[0034] The melting point of the hydroxyl-containing compound is preferably higher than the temperature at which the capacitor is used. The melting point of the hydroxyl-containing compound may be 50° C. or higher, and may be in the range of 80° C. to 300° C. (for example, in the range of 120° C. to 300° C.).

[0035] The hydroxyl group-containing compound may be at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol, and trimethylolpropane. The melting point of glucose is about 146 to 150°C, that of mannitol is about 165 to 169°C, that of sorbitol is about 93 to 95°C, that of xylitol is about 92 to 97°C, that of pentaerythritol is about 257 to 260°C, and that of trimethylolpropane is about 56 to 58°C. Note that the melting points of these substances may vary depending on the structure (stereoisomer). Glucose, mannitol, and pentaerythritol are preferred because they have high melting points.

[0036] (conductive polymer) Examples of conductive polymers include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, and derivatives thereof. The derivatives include polymers having polypyrrole, polythiophene, polyfuran, polyaniline, and polyacetylene as a basic skeleton. For example, derivatives of polythiophene include poly(3,4-ethylenedioxythiophene). These conductive polymers may be used alone or in combination. The conductive polymer may be a copolymer of two or more monomers. The weight-average molecular weight of the conductive polymer is not particularly limited, and may be in the range of, for example, 1,000 to 100,000. A preferred example of the conductive polymer is poly(3,4-ethylenedioxythiophene) (PEDOT).

[0037] A dopant may be added to the conductive polymer. From the viewpoint of suppressing dedoping from the conductive polymer, it is preferable to use a polymer dopant. Examples of polymer dopants include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, and the like. These may be used alone or in combination of two or more. These may be added in the form of a salt. The polymer dopant may exist in the electrolyte in the form of an anion in which a cation (e.g., a proton) is dissociated from at least a part of the acidic group. A preferred example of the dopant is polystyrene sulfonic acid (PSS).

[0038] The weight-average molecular weight of the dopant is not particularly limited, but may be in the range of 1,000 to 100,000 in order to facilitate the formation of a homogeneous electrolyte layer.

[0039] The conductive polymer may be poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid.

[0040] (Liquid component) The electrolytic capacitor may contain a non-aqueous solvent or an electrolytic solution as a liquid component. The liquid component may be a substance that is liquid at room temperature (25°C) or at the temperature at which the electrolytic capacitor is used. A preferred example of the liquid component is a liquid in which the hydroxyl group-containing compound is substantially insoluble. The liquid component has a role of protecting the conductive polymer. In addition, the inclusion of the liquid component can improve the contact between the conductive polymer and the dielectric layer, and can also improve the repairability of defects in the dielectric layer. The electrolytic solution can function as an electrolyte together with the conductive polymer.

[0041] The non-aqueous solvent may be an organic solvent or an ionic liquid. Examples of the non-aqueous solvent include polyhydric alcohols such as ethylene glycol and propylene glycol, cyclic sulfones such as sulfolane (SL), lactones such as γ-butyrolactone (GBL), amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, carbonate compounds such as propylene carbonate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, and formaldehyde.

[0042] Also, a polymer-based solvent may be used as the non-aqueous solvent. Examples of polymer-based solvents include polyalkylene glycol, derivatives of polyalkylene glycol, and compounds in which at least one hydroxyl group in a polyhydric alcohol is substituted with polyalkylene glycol (including derivatives). Specifically, examples of polymer-based solvents include polyethylene glycol (PEG), polyethylene glycol glyceryl ether, polyethylene glycol diglyceryl ether, polyethylene glycol sorbitol ether, polypropylene glycol, polypropylene glycol glyceryl ether, polypropylene glycol diglyceryl ether, polypropylene glycol sorbitol ether, and polybutylene glycol. Examples of polymer-based solvents further include ethylene glycol-propylene glycol copolymers, ethylene glycol-butylene glycol copolymers, and propylene glycol-butylene glycol copolymers. The non-aqueous solvent may be used alone or in a mixture of two or more.

[0043] The liquid component may contain an acid component and a base component. Examples of the acid component include maleic acid, phthalic acid, benzoic acid, pyromellitic acid, and resorcylic acid. Examples of the base component include 1,8-diazabicyclo[5,4,0]undecene-7, 1,5-diazabicyclo[4,3,0]nonene-5, 1,2-dimethylimidazolinium, 1,2,4-trimethylimidazoline, 1-methyl-2-ethyl-imidazoline, 1,4-dimethyl-2-ethylimidazoline, 1-methyl-2-heptylimidazoline, 1-methyl-2-(3'heptyl)imidazoline, 1-methyl-2-dodecylimidazoline, 1,2-dimethyl-1,4,5,6-tetrahydropyrimidine, 1-methylimidazole, and 1-methylbenzimidazole.

[0044] The electrolyte contains a non-aqueous solvent and a solute (e.g., an organic salt) dissolved therein. Examples of the non-aqueous solvent constituting the electrolyte include the examples of the non-aqueous solvents described above. Examples of the solute include inorganic salts and organic salts. An organic salt is a salt in which at least one of the anion and the cation contains an organic substance. Examples of the organic salt include trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazolinium phthalate, mono-1,3-dimethyl-2-ethylimidazolinium phthalate, and the like.

[0045] In order to suppress dedoping of the dopant, the pH of the liquid component may be less than 7, or may be 5 or less.

[0046] (anode foil) The anode foil may be a metal foil having a dielectric layer formed on its surface. The type of metal constituting the metal foil is not particularly limited. In terms of ease of forming the dielectric layer, examples of metals constituting the metal foil include valve metals such as aluminum, tantalum, niobium, and titanium, and alloys of valve metals. A preferred example is aluminum or an aluminum alloy. Usually, the surface of the anode foil is roughened, and the dielectric layer is formed on the roughened surface. The dielectric layer of the anode foil is in contact with a conductive polymer (electrolyte).

[0047] The anode foil can be obtained, for example, by roughening the surface of a metal foil by etching or the like, and then forming a dielectric layer (oxide film) on the roughened surface of the metal foil by chemical conversion treatment or the like.

[0048] (cathode foil) A metal foil can be used for the cathode foil. The type of metal constituting the metal foil is not particularly limited. Examples of metals constituting the metal foil include valve metals such as aluminum, tantalum, niobium, and titanium, and alloys of valve metals. A preferred example is aluminum and an aluminum alloy. In addition, a chemical conversion film may be provided on the surface of the cathode foil, and a coating of a metal (heterogeneous metal) or a nonmetal different from the metal constituting the cathode foil may be provided. Examples of heterogeneous metals and nonmetals include metals such as titanium and nonmetals such as carbon.

[0049] The electrolytic capacitor may be a wound electrolytic capacitor including a wound body formed by winding an anode foil and a cathode foil with a separator interposed between them, or a stacked electrolytic capacitor including a stack formed by folding an anode foil and a cathode foil in a zigzag shape with a separator interposed between them.

[0050] Here, Fig. 1 is a cross-sectional view that typically shows one example of an electrolytic capacitor according to an embodiment of the present invention. Fig. 2 is a perspective view that typically shows the configuration of the wound body of Fig. 2. Fig. 2 is a view in which a part of the wound body of Fig. 1 is developed.

[0051] Electrolytic capacitor 200 includes a wound body 100. Wound body 100 is formed by winding anode foil 10 and cathode foil 20 with separator 30 interposed therebetween.

[0052] The wound body 100 includes a conductive polymer (not shown) and a hydroxyl group-containing compound (not shown). That is, the conductive polymer and the hydroxyl group-containing compound are interposed between the anode foil 10 (dielectric layer) and the cathode foil 20, and are attached to the surface layer and inside of the separator 30. The hydroxyl group-containing compound is unevenly distributed in the separator 30.

[0053] One end of lead tabs 50A and 50B are connected to the anode foil 10 and the cathode foil 20, respectively, and the lead tabs 50A and 50B are wound to form the wound body 100. Lead wires 60A and 60B are connected to the other ends of the lead tabs 50A and 50B, respectively.

[0054] A stop tape 40 is disposed on the outer surface of the cathode foil 20 located in the outermost layer of the wound body 100, and the ends of the cathode foil 20 are fixed by the stop tape 40. When the anode foil 10 is prepared by cutting from a large foil, the wound body 100 may further be subjected to a chemical conversion treatment in order to provide a dielectric layer on the cut surface.

[0055] The wound body 100 is housed in the bottomed case 211 so that the lead wires 60A and 60B are located on the opening side of the bottomed case 211. The material of the bottomed case 211 can be a metal such as aluminum, stainless steel, copper, iron, brass, or an alloy of these metals.

[0056] A sealing member 212 is placed at the opening of bottomed case 211 in which wound body 100 is stored, the open end of bottomed case 211 is crimped to sealing member 212 and curled, and a seat plate 213 is placed on the curled portion, thereby sealing wound body 100 inside bottomed case 211.

[0057] The sealing member 212 is formed so that the lead wires 60A and 60B penetrate through it. The sealing member 212 may be made of any insulating material, and is preferably made of an elastic material. Among them, silicone rubber, fluororubber, ethylene propylene rubber, hypalon rubber, butyl rubber, isoprene rubber, etc., which have high heat resistance, are preferred.

[0058] [Manufacturing method of electrolytic capacitors] A method for producing an electrolytic capacitor according to an embodiment of the present invention includes a first step of obtaining a capacitor element intermediate (hereinafter also simply referred to as intermediate), and a second step of impregnating the intermediate with a treatment liquid containing a conductive polymer to obtain a capacitor element. The intermediate includes an anode foil having a dielectric layer on its surface, a cathode foil, a separator interposed between the anode foil and the cathode foil, and a hydroxyl-containing compound attached to the surface and inside of the separator and unevenly distributed in the separator. It can also be said that the intermediate includes an electrode group and a hydroxyl-containing compound. The separator includes synthetic fibers and cellulosic fibers. The hydroxyl-containing compound is at least one compound (excluding polymers) selected from the group consisting of sugars and polyhydric alcohols.

[0059] By carrying out the first and second steps, a capacitor element can be obtained in which the separator contains a large amount of conductive polymer.

[0060] (1st step) (Step (1a)) An example of the first step may include a step (1a) of obtaining an electrode group by disposing a separator between an anode foil and a cathode foil, and impregnating the electrode group with a treatment liquid containing a hydroxyl group-containing compound. Step (1a) may be performed repeatedly.

[0061] In step (1a), for example, the electrode group is immersed in a treatment liquid containing a hydroxyl group-containing compound. The immersion time is, for example, 1 minute or more and less than 20 minutes. Step (1a) may be performed at room temperature or at a temperature other than room temperature (for example, a temperature higher than room temperature). Step (1a) may be performed under atmospheric pressure or under reduced pressure.

[0062] The treatment liquid containing a hydroxyl group-containing compound used in step (1a) usually contains water. Hereinafter, the treatment liquid containing a hydroxyl group-containing compound is also referred to as an "aqueous treatment liquid". The amount of water contained in the liquid (solvent) constituting the aqueous treatment liquid is, for example, in the range of 50 to 100% by mass. Usually, the hydroxyl group-containing compound is dissolved in the aqueous treatment liquid, and the aqueous treatment liquid is an aqueous solution of the hydroxyl group-containing compound. The content (concentration) of the hydroxyl group-containing compound in the aqueous treatment liquid may be in the range of 3 to 50% by mass (for example, in the range of 5 to 15% by mass). The aqueous treatment liquid may contain components other than the hydroxyl group-containing compound as necessary.

[0063] The aqueous treatment liquid does not contain a polymer (a polymer with a weight-average molecular weight of 1000 or more). For example, the aqueous treatment liquid does not contain a conductive polymer. Since the aqueous treatment liquid that does not contain a polymer has a low viscosity, it is easy to impregnate the electrode group and the hydroxyl group-containing compound is easily attached to the inside of the separator.

[0064] (Step (2a)) An example of the first step may include, after step (1a), step (2a) of heating and drying the electrode group impregnated with the treatment liquid containing the hydroxyl group-containing compound. Step (2a) may produce an intermediate containing the electrode group and the hydroxyl group-containing compound. Step (2a) may be performed under atmospheric pressure or under reduced pressure. The heating temperature in step (2a) is, for example, 100°C or higher, 120°C or higher, or 125°C or higher. From the viewpoint of easily penetrating the hydroxyl group-containing compound into the inside of the separator (capacitor element), the heating and drying in step (2a) may be performed at a temperature equal to or higher than the melting point of the hydroxyl group-containing compound.

[0065] The first step may include a step of heating the separator to carbonize it. Usually, the separator is partially carbonized. The carbonization can adequately reduce the density of the separator and increase the absorbency of the treatment liquid containing the hydroxyl group-containing compound and the treatment liquid containing the conductive polymer. In the carbonization, the cellulosic fibers are mainly carbonized.

[0066] The carbonization of the separator may be carried out, for example, by heating the intermediate after step (2a). Step (2a) may also serve as a step of carbonizing the separator. The heating temperature for the carbonization is preferably 130° C. or higher and 280° C. or lower, more preferably 160° C. or higher and 230° C. or lower. The heating time for the carbonization is, for example, 80 minutes or higher and 100 minutes or lower.

[0067] Furthermore, if the separator contains binder fibers, the first step may include a step of heating the separator to heat-seal the binder fibers, thereby bonding the fibers in the separator together and increasing the strength of the separator. The heat-sealing treatment of the binder fibers is performed, for example, before step (1a) (forming the electrode group).

[0068] (Process (1b)) Another example of the first step may include a step (1b) of obtaining a separator having a hydroxyl-containing compound attached to the surface and inside thereof.

[0069] Step (1b) may include step (1b-1) of impregnating the separator with a treatment liquid containing a hydroxyl group-containing compound. Step (1b-1) may be repeated. In step (1b-1), for example, the treatment liquid containing a hydroxyl group-containing compound is applied or sprayed onto the separator. The treatment liquid containing a hydroxyl group-containing compound in step (1b) may be the same as the treatment liquid containing a hydroxyl group-containing compound used in step (1a).

[0070] Step (1b) may include, after step (1b-1), a step (1b-2) of heating and drying the separator impregnated with the treatment liquid containing the hydroxyl-containing compound. Step (1b-2) may be performed under atmospheric pressure or under an environment other than atmospheric pressure (e.g., reduced pressure). The heating temperature in step (1b-2) is, for example, 100°C or higher, 120°C or higher, or 125°C or higher. The heating and drying in step (1b-2) may be performed at a temperature equal to or higher than the melting point of the hydroxyl-containing compound. When the separator contains binder fibers, step (1b-2) may also serve as a step of heat-sealing the binder fibers.

[0071] Moreover, the step (1b) includes a blending step of blending synthetic fibers and cellulosic fibers to obtain a separator, and a hydroxyl group-containing compound may be added in the blending step.

[0072] Another example of the first step may include a step (2b) of disposing a separator between the anode foil and the cathode foil after the step (1b). An intermediate body in which the hydroxyl group-containing compound is unevenly distributed on the separator may be obtained by the step (2b). Also, a step of carbonizing the separator after the step (2b) may be included. The carbonization of the separator can be performed by heating the intermediate body.

[0073] In the case of a wound type capacitor, the anode foil and the cathode foil may be wound with a separator interposed between them to form an electrode group (wound body). In the case of a laminated type capacitor, the anode foil and the cathode foil may be folded in a zigzag pattern to form an electrode group (laminate) with a separator interposed between them.

[0074] (2nd process) In the second step, the intermediate is impregnated with a treatment liquid containing a conductive polymer to obtain a capacitor element. In the second step, for example, the intermediate may be immersed in the treatment liquid containing a conductive polymer. The immersion time is, for example, 30 seconds or more and 30 minutes or less. The second step may be performed at room temperature or at a temperature other than room temperature (for example, a temperature higher than room temperature). In addition, the second step may be performed under atmospheric pressure or under reduced pressure.

[0075] The treatment liquid containing a conductive polymer usually contains water. Hereinafter, the treatment liquid containing a conductive polymer is also referred to as an "aqueous dispersion". The amount of water contained in the aqueous liquid (dispersion medium) constituting the aqueous dispersion is, for example, in the range of 2 to 100 mass %. The aqueous liquid may be water. The conductive polymer is dispersed in the aqueous liquid. That is, the aqueous dispersion is a suspension in which the conductive polymer is dispersed in the aqueous liquid. The content (concentration) of the conductive polymer in the aqueous dispersion may be in the range of 0.1 to 20 mass % (for example, in the range of 0.5 to 3 mass %).

[0076] The viscosity of the aqueous dispersion may be in the range of 1 mPa·s to 100 mPa·s, or in the range of 1 mPa·s to 40 mPa·s (for example, in the range of 1 mPa·s to 25 mPa·s). The lower the viscosity of the aqueous dispersion, the easier it is to impregnate the intermediate.

[0077] The aqueous dispersion does not need to contain a hydroxyl group-containing compound. By not adding a hydroxyl group-containing compound, the viscosity of the aqueous dispersion can be reduced, the aqueous dispersion can be easily impregnated, and the conductive polymer can be easily impregnated into the intermediate (inside the separator). When the electrode group is impregnated with a mixed treatment liquid in which a hydroxyl group-containing compound is added to the aqueous dispersion, it is difficult to attach the conductive polymer to the inside of the separator, and the ESR increases.

[0078] A dopant may be added to the conductive polymer. The aqueous dispersion may contain components other than the conductive polymer and the dopant, as necessary.

[0079] The second step may further include a step of drying the aqueous dispersion impregnated in the intermediate. The drying of the aqueous dispersion may be performed under atmospheric pressure or under reduced pressure. The drying of the aqueous dispersion may be performed by heating the aqueous dispersion impregnated in the intermediate. The heating temperature is, for example, 100°C or higher and 120°C or lower.

[0080] (3rd step) The method for producing an electrolytic capacitor may include a third step of impregnating the capacitor element with a liquid component (a non-aqueous solvent or an electrolytic solution). The third step may be carried out, for example, by injecting the liquid component into a bottomed case for an electrolytic capacitor in which the capacitor element is housed. The non-aqueous solvent or the electrolytic solution may be one exemplified above. The method for producing an electrolytic capacitor may include a step of sealing the bottomed case in which the capacitor element is housed.

[0081] [Example] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0082] Examples 1 to 4 A wound-type electrolytic capacitor (diameter 10 mm × length 10 mm) with a rated voltage of 35 V and a rated capacitance of 270 μF was fabricated by the following procedure.

[0083] (Preparation of cathode foil) The cathode foil used was an Al foil (aluminum foil) having a thickness of 50 μm.

[0084] (Preparation of anode foil) An Al foil having a thickness of 120 μm was prepared. This Al foil was subjected to a direct current etching process to roughen the surface. Next, the Al foil was subjected to a chemical conversion process to form a dielectric layer (thickness: about 70 nm), thereby obtaining an anode foil. The dielectric layer was formed by immersing the Al foil in an ammonium adipate solution and performing a chemical conversion process at 70° C. for 5 hours while applying a voltage of 50 V to the Al foil. The anode foil was then cut to a predetermined size to prepare an anode foil.

[0085] (Preparation of separator) A nonwoven fabric (separator) was obtained by mixing aramid fibers, natural cellulose fibers, and PET fibers in the mass ratio shown in Table 1. In Table 1, a1 to a4 respectively represent the separators produced in Examples 1 to 4. The thickness of the separators a1 to a4 was 40 μm.

[0086] (Making of the roll) An anode lead tab and a cathode lead tab connected to a lead wire were connected to the prepared anode foil and cathode foil, respectively. Then, the anode foil and the cathode foil were wound with a separator sandwiched therebetween, and the outer surface was fixed with a winding stop tape. In this way, a wound body was produced. Next, the wound body was heated at 200°C for 90 minutes in the air to carbonize the separator. Next, the wound body was immersed in an ammonium adipate solution, and a voltage of 50V was applied to the anode foil, and a chemical conversion treatment was performed again at 70°C for 60 minutes, thereby forming a dielectric layer mainly on the end surface of the anode foil.

[0087] (Preparation of treatment solution containing hydroxyl group-containing compound) Mannitol was dissolved in ion-exchanged water to prepare an aqueous mannitol solution (concentration: 10% by mass) as a treatment liquid containing a hydroxyl group-containing compound. The viscosity of the resulting aqueous mannitol solution was 5 mPa·s or less.

[0088] (Preparation of treatment solution containing conductive polymer) 3,4-ethylenedioxythiophene and polystyrene sulfonic acid as a dopant were dissolved in ion-exchanged water to prepare a mixed solution. While stirring the obtained mixed solution, iron (III) sulfate (oxidant) dissolved in ion-exchanged water was added to carry out a polymerization reaction. After the reaction, the obtained reaction solution was dialyzed to remove unreacted monomers and excess oxidant, and a dispersion (aqueous dispersion) containing poly(3,4-ethylenedioxythiophene) doped with about 5% by mass of polystyrene sulfonic acid (PSS) was obtained. In the following, poly(3,4-ethylenedioxythiophene) doped with about 5% by mass of polystyrene sulfonic acid (PSS) may be referred to as "PEDOT:PSS". In addition, the dispersion in which PEDOT:PSS is dispersed may be referred to as "PEDOT:PSS dispersion". Using this PEDOT:PSS dispersion, an aqueous dispersion with a PEDOT:PSS concentration of 2% by mass was prepared as a treatment liquid containing a conductive polymer. The viscosity of the resulting aqueous dispersion was 25 mPa·s.

[0089] (Preparation of capacitor element intermediate) The wound body was immersed in the aqueous mannitol solution in a container at room temperature under atmospheric pressure for 5 minutes, and then dried at 200°C for 20 minutes in a drying oven at 1 atm (first step). In this way, mannitol was attached to the wound body (surface and interior of the separator) to obtain an intermediate. The melting point of mannitol is about 165 to 169°C, and the drying temperature for the wound body is higher than the melting point of mannitol.

[0090] (Fabrication of capacitor elements) The intermediate was immersed in the PEDOT:PSS dispersion in a container at room temperature for 15 minutes in a reduced pressure atmosphere (40 kPa), and then dried at 150°C for 30 minutes in a drying oven at 1 atm (second step). In this way, a conductive polymer was attached to the intermediate (surface and interior of the separator), and a capacitor element was obtained.

[0091] When the distribution of mannitol in the capacitor element was examined by the method described above, it was confirmed that mannitol was unevenly distributed in the separator. O / M I was 0.78 to 0.85.

[0092] (Impregnation of liquid components) The capacitor element was placed in a bottomed case and impregnated with a liquid component at room temperature under atmospheric pressure. The liquid component was a mixed solvent of GBL and SL (mass ratio 50:50).

[0093] (Capacitor sealing) A sealing member and a seat plate were placed in the opening of the bottomed case to seal the capacitor element. In this way, an electrolytic capacitor was completed. After that, an aging treatment was performed at 130°C for 2 hours while applying the rated voltage. In addition, A1 to A4 in Table 1 represent the electrolytic capacitors of Examples 1 to 4, respectively.

[0094] Comparative Example 1 Mannitol was dissolved in the PEDOT:PSS dispersion to prepare a mixed solution of PEDOT:PSS and mannitol. In the mixed solution, the concentration of PEDOT:PSS was 2% by mass, and the concentration of mannitol was 10% by mass. The viscosity of the mixed solution was 58 mPa s.

[0095] A wound body was produced in the same manner as in Example 1, except that separator a2 was used instead of separator a1. Without carrying out the first and second steps, the wound body was immersed in the mixed treatment solution in a container at room temperature in a reduced pressure atmosphere (40 kPa) for 15 minutes, and then dried in a drying oven at 1 atm for 30 minutes at 150° C. In this way, the conductive polymer and mannitol were attached to the wound body (surface and interior of the separator), and a capacitor element was obtained.

[0096] When the distribution of mannitol in the capacitor element was examined by the method described above, it was found that mannitol was not unevenly distributed in the separator. O / M I was 1.0.

[0097] An electrolytic capacitor X1 was produced in the same manner as in Example 1 using the capacitor element obtained above.

[0098] Comparative Example 2 An electrolytic capacitor X2 was produced in the same manner as in Example 1, except that a separator x1 made of aramid fiber was used instead of the separator a1.

[0099] Comparative Example 3 The wound body used was the same as that in Comparative Example 2, including the separator x1. Without carrying out the first and second steps, the wound body was immersed in the same mixed treatment liquid as that in Comparative Example 1 for 15 minutes at room temperature in a reduced pressure atmosphere (40 kPa), and then dried at 150°C for 30 minutes in a drying oven with a pressure of 1 atmosphere. In this way, the conductive polymer and mannitol were attached to the wound body (surface and inside of the separator), and a capacitor element was obtained. An electrolytic capacitor X3 was produced in the same manner as in Example 1 using the capacitor element obtained above.

[0100] Comparative Example 4 An electrolytic capacitor X4 was produced in the same manner as in Example 1, except that a separator x2 made of natural cellulose fiber was used instead of the separator a1.

[0101] The electrolytic capacitors thus fabricated were evaluated as follows. [Breakdown voltage] A voltage was applied while increasing it at a rate of 1.0 V / sec, and the breakdown voltage (BDV) (V) at which an overcurrent of 0.5 A flows was measured.

[0102] [Initial capacitance and ESR] The initial capacitance (C0) (μF) and ESR (R0) (mΩ) were measured using a four-terminal LCR meter in an environment of 20°C.

[0103] [ΔESR] A load test was performed by applying a rated voltage of 35V to the capacitor for 500 hours in a 150℃ environment. After 500 hours, the ESR (R1) was measured using the same method as above. The ratio of R1 to R0, R1 / R0, was calculated and used as ΔESR.

[0104] [Short circuit occurrence rate] Thirty pieces of each of the eight types of capacitors were made and subjected to the same load test as above. After 500 hours, each capacitor was checked for the presence or absence of short circuits. The number of short-circuited capacitors out of the 30 capacitors was then counted, and the proportion of short-circuits was calculated as the short circuit occurrence rate.

[0105] The evaluation results are shown in Table 1.

[0106] [Table 1]

[0107] The electrolytic capacitors A1 to A4 exhibited high capacitance, high BDV, and low ESR. Furthermore, the electrolytic capacitors A1 to A4 exhibited a small increase in ΔESR and a low incidence of short circuits.

[0108] The ESR increased in electrolytic capacitors X1 and X3. This is thought to be because the wound body was immersed in a mixed treatment solution of PEDOT:PSS and mannitol, which prevented the separator from containing a large amount of PEDOT:PSS.

[0109] In electrolytic capacitors X2 and X3 using separator x1 (synthetic fibers only), the capacitance dropped significantly and the ESR increased. This is thought to be because the effect of the synthetic fibers containing PVA was greater in separator x1, making it impossible to contain a large amount of mannitol in the separator. In electrolytic capacitor X4 using separator x2 (natural fibers only), the BDV was low and the incidence of short circuits increased. [Industrial Applicability]

[0110] The present invention can be used for an electrolytic capacitor and a method for manufacturing the same. [Explanation of symbols]

[0111] 10: anode foil, 20: cathode foil, 30: separator, 40: winding stop tape, 50A, 50B: lead tabs, 60A, 60B: lead wires, 100: wound body, 200: electrolytic capacitor, 211: bottomed case, 212: sealing member, 213: seat plate

Claims

1. a capacitor element including an anode foil having a dielectric layer on a surface thereof, a cathode foil, a separator interposed between the anode foil and the cathode foil, a hydroxyl group-containing compound, and a conductive polymer; The separator includes synthetic fibers and cellulosic fibers, the conductive polymer and the hydroxyl group-containing compound are attached to a surface layer and an inside of the separator, the hydroxyl group-containing compound is at least one compound (excluding polymers) selected from the group consisting of sugars and polyhydric alcohols, The electrolytic capacitor, wherein the hydroxyl group-containing compound is unevenly distributed in the separator.

2. In the capacitor element, the mass ratio M of the hydroxyl group-containing compound to the conductive polymer inside the separator I is the mass ratio M of the hydroxyl group-containing compound to the conductive polymer in the surface layer of the separator. O 2. The electrolytic capacitor of claim 1 , wherein

3. The mass ratio M I The mass ratio M O Ratio of: M O / M I The electrolytic capacitor according to claim 2 , wherein is equal to or greater than 0.7 and is equal to or less than 0.

9.

4. 4. The electrolytic capacitor according to claim 1, wherein the synthetic fibers include at least one selected from the group consisting of aramid, polyethylene terephthalate, and vinylon.

5. The electrolytic capacitor of any one of claims 1 to 4, wherein the synthetic fibers are fibrillated.

6. 6. The electrolytic capacitor according to claim 1, wherein the hydroxyl group-containing compound includes at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol, and trimethylolpropane.

7. The electrolytic capacitor of any one of claims 1 to 6, wherein the conductive polymer comprises poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid.

8. The electrolytic capacitor according to claim 1 , wherein the capacitor element contains a non-aqueous solvent or an electrolytic solution.

9. a first step of obtaining an intermediate including an anode foil having a dielectric layer on a surface thereof, a cathode foil, a separator interposed between the anode foil and the cathode foil, and a hydroxyl group-containing compound attached to a surface layer and an interior of the separator and unevenly distributed in the separator; a second step of impregnating the intermediate with a treatment liquid containing a conductive polymer to obtain a capacitor element; The separator includes synthetic fibers and cellulosic fibers, The method for producing an electrolytic capacitor, wherein the hydroxyl group-containing compound is at least one compound (excluding polymers) selected from the group consisting of sugars and polyhydric alcohols.

10. 10. The method for producing an electrolytic capacitor according to claim 9, wherein the first step includes a step (1a) of obtaining an electrode group by disposing the separator between the anode foil and the cathode foil, and impregnating the electrode group with a treatment liquid containing the hydroxyl group-containing compound.

11. 11. The method for producing an electrolytic capacitor according to claim 10, wherein the first step includes, after the step (1a), a step (2a) of heating and drying the electrode group impregnated with the treatment liquid containing the hydroxyl group-containing compound at a temperature equal to or higher than a melting point of the hydroxyl group-containing compound.

12. The method for producing an electrolytic capacitor according to any one of claims 9 to 11, wherein the first step includes a step of carbonizing the separator.

13. The first step comprises: (1b) obtaining the separator having the hydroxyl group-containing compound attached to the surface and the inside of the separator; After the step (1b), a step (2b) of disposing the separator between the anode foil and the cathode foil; The method for producing the electrolytic capacitor according to claim 9 , comprising:

14. The method for producing an electrolytic capacitor according to claim 13, wherein the step (1b) includes a step (1b-1) of impregnating the separator with a treatment liquid containing the hydroxyl group-containing compound.

15. The method for producing an electrolytic capacitor according to claim 14, wherein the step (1b) includes, after the step (1b-1), a step (1b-2) of heating and drying the separator impregnated with the treatment liquid containing the hydroxyl group-containing compound at a temperature equal to or higher than a melting point of the hydroxyl group-containing compound.

16. The method for producing an electrolytic capacitor according to claim 15, further comprising the step of carbonizing the separator after the step (2b).

17. The step (1b) includes a blending step of blending the synthetic fibers and the cellulosic fibers to obtain the separator, The method for producing an electrolytic capacitor according to any one of claims 13 to 16, wherein the hydroxyl group-containing compound is added in the mixing step.

18. The method for producing an electrolytic capacitor according to any one of claims 9 to 17, further comprising a third step of impregnating the capacitor element with a non-aqueous solvent or an electrolytic solution.

19. The method for producing an electrolytic capacitor according to any one of claims 9 to 18, wherein the synthetic fiber includes at least one selected from the group consisting of aramid, polyethylene terephthalate, and vinylon.

20. The method for producing an electrolytic capacitor according to any one of claims 9 to 19, wherein the synthetic fibers are fibrillated.

21. The method for producing an electrolytic capacitor according to any one of claims 9 to 20, wherein the hydroxyl group-containing compound includes at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol, and trimethylolpropane.

22. The method for producing an electrolytic capacitor according to any one of claims 9 to 21, wherein the conductive polymer comprises poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid.

Citation Information

Patent Citations

  • Method of manufacturing capacitor

    JP2001110683A

  • Separator and solid electrolytic capacitor using the same

    JP2010153427A

  • Solid electrolytic capacitor and method of manufacturing the same

    JP2010245150A

  • Separator for electric double layer capacitor

    WO2007061108A1

  • Process for producing solution having electrically conductive polymer dispersed therein, and electrolytic capacitor

    WO2012140881A1